Investigations into soccer aerodynamics via trajectory analysis and dust experiments - Goff, J. E.; Carré, M. J. (Procedia Engineering, 2012)
We present a summary of our investigations into the aerodynamics of soccer balls (association footballs). Using a ball launcher and high-speed cameras, we are able to determine drag and lift coefficients using trajectory analysis. Advantages of this approach over wind tunnels include studying balls in flight without a support rod, which may influence aerodynamic studies in wind tunnels, and the ability to determine lift coefficients in regions inaccessible by many wind tunnels. We have found lift coefficients for spin parameters between 0 and 1 and Reynolds numbers between 130,000 and 300,000. Launching a ball into a dust cloud allows for the study of boundary-layer separation, again without the need of a support rod, which is needed for wind-tunnel studies. We have found boundary-layer separation angles in and around the drag crisis. Anomalous behavior is seen just past the drag crisis.